Across the river and into the trees - Hemingway, Ernest Miller, 1899-1961.; Arrow Books (London : Arrow Books, 2004)
A story of an American colonel stationed in Italy at the end of World War II, whose fifty years and heart condition weigh heavily upon him as he spends a weekend in Venice.
English.
Keywords: Man-woman relationships -- Fiction; Fiction, English; Military personnel -- Fiction; War stories; World War, 1939-1945 -- Italy -- Fiction